VD_FINDINFO HC / 2015 / 155 vom 3. März 2015 - VD Tribunal cantonal (2015)
CONTRAT D'ENTREPRISE, PRIX EFFECTIF, VOLONTÉ RÉELLE, FARDEAU DE LA PREUVE, PRIX FERME, FRAIS JUDICIAIRES | 18 CO, 373 CO, 374 CO, 375 CO, 15 al. 1 TFJC, 18 al. 1 TFJC, 111 al. 1 CPC (CH), 111 al. 2 CPC (CH), 95 CPC (CH)